صفات سے متعلقہ آیاتِ متشابہات فکری مناہج کا تجزیاتی مطالعہ - Amir Hamza (Mujalla Islami Fikr-o-Tahzeeb (MIFT) / مجلہ اسلامی فکر و تہذیب, 2021)
The Holy Quran is a complete code of life. It gives the humankind physical, moral and spiritual guidance. It also introduces the creature of the universe in vast detail by citing His names, His attributes, His highness and His omnipotence etc. All the attributes pertaining to Allah mentioned in the Holy Quran is divided into two kinds; Rational Attributes and Revealed Attributes. Rational Attributes mean Divine Characteristics that are cited in the Holy text and justified by logic and reasoning as well, e.g., The All Aware, The Omniscient, The All Seeing etc. Revealed Attributes mean the divine Characteristics known by only revealed sources and reason has no access to prove them, e.g., His Hand (yad), His Face (wajh), His rising over (istiwa) the Throne, etc.There is almost consensus on the perception of Rational Attributes, but the second one is highly controversial and debatable in the manner of its understanding. Regardless of Mujassimah and Muattilah (the both are at the extreme ends), there is no unanimity in the school of Ahl ul Sunnah also. We find three major opinion to deal with these attributes:Tafweed: the real meanings of attributes are entrusted to Allah and not be discussed.Taweel: the attributes can be interpreted carefully, so that people could be protected from any deviation.Ithbat: meanings of attributes are determined as same we find in dictionary, but the how-ness is entrusted to Allah.The First Two opinions regarding to the majority of Ahl ul Sunnah, while the last is reported from some Hanbli scholars and contemporary Salfi scholars. This article analyses all three opinions deeply.Key words: Holy Qur'an  Humankind spiritual Guidance God's Attributes  Characteristics